Determinantes da incidência e intensidade de infestação por ervas-de-passarinho na arborização urbana do município de Santarém-Pará-Brasill - SILVA, Francisco Pinheiro da (Universidade Federal do Oeste do Pará, 2024)
One of the problems that affect the quality of urban trees is 31 infestation by mistletoes. Description of the main infested trees, and identification 32 of causes of infestation patterns, can help controlling and planning new 33 plantations of trees. This study aimed to answer the following questions: 1-What 34 8 species of mistletoes are found in the municipality of Santarem-PA-Brazil? 2-What 35 is the proportion and intensity of infestation of trees? and 3-Differences in 36 infestation rates between tree species can be explained by mistletoe-tree 37 compatibility? We sampled trees (> 3 m of height) in the main avenues of this city. 38 For each tree, we assessed the incidence and intensity of infestation. In order to 39 evaluate if the mistletoe-tree compatibility is the main determinant of the 40 parasitism patterns, we selected three species of trees for conducting a seed 41 inoculation experiment: Handroanthus serratifolius, Mangifera indica and 42 Andira inermis. Three infestation by Passovia theloneura Tiegh. was 19.3%, and 43 exotic species were more infested than native. The inoculation experiment showed 44 that the incompatibility between P. theloneura and H. serratifolius is primarily 45 responsible for its non-infestation. Mistletoes germinated in A. inermis grown 46 better than in M. indica, result contrary to the prevalence found in the field, 47 suggesting that pattern of infestation is also influenced by seed deposition 48 patterns.